Tratamiento del priapismo isquémico en el ecuador - Iza Jiménez, Bryan Antonio (2024)
Ischemic priapism consists of a persistent uncontrolled erection of the penis whether or not it is due to sexual stimulation, triggering processes of inflammation, ischemia and finally, necrosis of the corpora cavernosa, representing a urological emergency. Objective: to carry out an updated review of the treatment of ischemic priapism and its impact on the prognosis in Ecuador, in order to improve the quality of life of patients. Methodology: this is a predominantly qualitative, non-experimental study, it was based on the analysis of scientific articles extracted from different databases such as PubMed, Scielo, Science Direct, MedLine, within the last 5 years. Results: aspiration/instillation of isotonic saline plus intracavernous injection of a sympathomimetic (phenylephrine of choice) is the first line treatment for the management of ischemic priapism. In Ecuador, since phenylephrine is not available, adrenaline, noradrenaline and ephedrine are chosen. Conclusions: ischemic priapism is a rare urological emergency, but requires rapid and effective management, which, in the most complex scenario, would require surgical intervention, in order to preserve the function of the cavernous smooth muscle for adequate and optimal quality of life for man.